2002
DOI: 10.1002/mds.10089
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine transporter density is decreased in parkinsonian patients with a history of manganese exposure: What does it mean?

Abstract: Manganese (Mn) exposure can cause parkinsonism. Pathological changes occur mostly in the pallidum and striatum. Two patients with a long history of occupational Mn exposure presented with Mn-induced parkinsonism. In one patient, magnetic resonance imaging (MRI) showed findings consistent with Mn exposure, and Mn concentration was increased in the blood and urine. However, this patient's clinical features were typical of idiopathic Parkinson disease (PD). Previous pathological and positron emission tomography s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
76
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(80 citation statements)
references
References 40 publications
4
76
0
Order By: Relevance
“…PET studies examining [18F]-6-fluoro-L-DOPA uptake in patients suffering from manganism (Shinotoh et al 1997) and in Mn-intoxicated monkeys (Shinotoh et al 1995) reported intact dopamine transporter function on pre-synaptic terminals in the striatum. In contrast, Kim et al (2002) observed a decrease in binding of [123I]-1r-2β-carboxymethoxy-3β-(4-iodophenyl)tropane to pre-synaptic dopamine transporters using SPECT in two patients with chronic manganism, indicating either a direct effect on pre-synaptic nigrostriatal dopaminergic neurons or perhaps Mn intoxication with symptoms manifesting from underlying idiopathic Parkinson's disease. However, post-synaptic injury is most frequently observed in human Mn intoxication, noted studies by Kessler et al (2003), who demonstrated markedly reduced striatal post-synaptic D2-receptor density by [18F]-methylspiperone PET imaging in an advanced case of chronic manganism.…”
Section: Disruption Of Synaptic Transmission and Glial-neuronal Commumentioning
confidence: 81%
“…PET studies examining [18F]-6-fluoro-L-DOPA uptake in patients suffering from manganism (Shinotoh et al 1997) and in Mn-intoxicated monkeys (Shinotoh et al 1995) reported intact dopamine transporter function on pre-synaptic terminals in the striatum. In contrast, Kim et al (2002) observed a decrease in binding of [123I]-1r-2β-carboxymethoxy-3β-(4-iodophenyl)tropane to pre-synaptic dopamine transporters using SPECT in two patients with chronic manganism, indicating either a direct effect on pre-synaptic nigrostriatal dopaminergic neurons or perhaps Mn intoxication with symptoms manifesting from underlying idiopathic Parkinson's disease. However, post-synaptic injury is most frequently observed in human Mn intoxication, noted studies by Kessler et al (2003), who demonstrated markedly reduced striatal post-synaptic D2-receptor density by [18F]-methylspiperone PET imaging in an advanced case of chronic manganism.…”
Section: Disruption Of Synaptic Transmission and Glial-neuronal Commumentioning
confidence: 81%
“…Several valuable studies [1][2][3][4][5][6] have been published on the relation of manganese (Mn) exposure with high signal intensities on T1-weighted brain magnetic resonance images (MRI) in Korea since the detection of high signals in Korean welders exposed to Mn in 1997. However, the fact that high signal intensities on T1-weighted MRI can be a useful biomarker of exposure to Mn was relatively unknown in the field of occupational medicine.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier data showed that this method can distinguish IPD patients from normal controls (Jeon et al, 1998a(Jeon et al, , 1998b. Further, striatal DAT uptake is nearly normal in patients with Mn-induced parkinsonism, but is markedly reduced in IPD patients (Huang et al, 2003 (Huang et al, 2003;Kim et al, 2002). DAT SPECT is more easily accessible and less expensive than is fluorodopa PET.…”
Section: Pet/spect As An Index Of the Integrity Of The Dopaminergic Nmentioning
confidence: 98%
“…It is unclear whether secondary manganism caused by liver cirrhosis, for example, differs (from a neuroimaging standpoint) from manganism associated with occupational or environmental exposure to Mn. Some welders showed clinical features and PET/SPECT findings typical of IPD, with concurrent Mn exposure (Kim et al, 1999b(Kim et al, , 2002Racette et al, 2001). Initially, Kim et al (1999b) reported that one welder showed IPD with incidental exposure to Mn.…”
Section: Pet/spect As An Index Of the Integrity Of The Dopaminergic Nmentioning
confidence: 99%
See 1 more Smart Citation